Functional and Prognostic Assessment in Comatose Patients: A Study Using Somatosensory Evoked Potentials - Arciniegas-Villanueva, Andrea Victoria; Fernández-Diaz, Eva María; Gonzalez-Garcìa, Emilio; Sancho-Pelluz, Javier; Mansilla-Lozano, David; Segura, Tomás (Frontiers in Human Neuroscience, 2022)
Aim: The functional prognosis in patients after coma following either cardiac arrest (CA) or acute structural brain injury (ABI) is often uncertain. These patients are associated with high mortality and disability. N20 and N70 somatosensory evoked potentials (SSEP) are used to predict prognosis. We evaluated the utility of SSEP (N20-N70) as an early indicator of long-term prognosis in these patients. Methods: This was a retrospective cohort study of patients (n=120) admitted to the intensive care unit (ICU) with a diagnosis of coma after CA (n=60) or ABI (n=60). An SSEP study was performed including N20 and N70 at 24-72 hours after coma onset. Functional recovery was assessed 6-12 months later using the modified Glasgow scale (mGS). The study was approved by our local research ethics committee. Results: In the CA and ABI groups, the absence of N20 (36% of CA patients and 41% of ABI patients; specificity=100%) or N70 (68% of CA patients and 78% of ABI patients) was a strong indicator of poor outcome. Conversely, the presence of N70 was an indicator of a good outcome (AC: specificity=84.2%, sensitivity=92.7%; ABI: specificity=64.2% sensitivity=91.3%). Conclusion: Somatosensory evoked potentials are useful early prognostic markers with high specificity (N20) and sensitivity (N70). Moreover, N70 has additional potential value for improving the prediction of good long-term functional outcomes.